2021
DOI: 10.1111/jsr.13338
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment and assault predict sleep disturbances and is partly mediated by nightmares: Findings from a national survey of all university students in Norway

Abstract: Summary Sexual harassment and assault is common in most domains of society, and has been linked to several adverse outcomes, including reduced sleep quality. However, less is known about the possible impact of sexual harassment and assault on various sleep problems among university students. In a sample of 49,051 students in Norway (69.2% women), we examined i) the associations of varying extents of sexual harassment (unwanted sexual comments, looks or gestures, photographs, indecent exposure, and physical har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…breasts or buttocks), female students experienced more verbal sexual harassment. This is in accordance with research findings that the most frequently reported sexual harassment is unwanted comments/verbal and physical harassment [56]. According to another survey, up to 72% of respondents have been verbally abused.…”
Section: Figure 2 Summary Of the Relationship Between Variablessupporting
confidence: 91%
“…breasts or buttocks), female students experienced more verbal sexual harassment. This is in accordance with research findings that the most frequently reported sexual harassment is unwanted comments/verbal and physical harassment [56]. According to another survey, up to 72% of respondents have been verbally abused.…”
Section: Figure 2 Summary Of the Relationship Between Variablessupporting
confidence: 91%
“…The current results also indicate that 21.4% ( n = 282) of participating RCMP reported being sexually harassed while on duty and 7.1% ( n = 94) reported being sexually harassed during the CTP. The current results may have implications for RCMP mental health, as sexual victimization is associated with several mental health challenges (Dworkin, 2020; Steine et al, 2021). RCMP cadets may be at less risk for sexual victimization during the CTP because their exposures to civilians are less frequent than experienced by serving RCMP while on duty; however, the current results indicate that cadets also experience sexual assault and sexual harassment during their participation in the CTP and that, for many, the perpetrator was an organizational superior, coworker, peer, or even subordinate within the RCMP.…”
Section: Discussionmentioning
confidence: 88%
“…It can discourage victims from reporting incidents of sexual harassment and can perpetuate a culture of silence around the issue. A national survey by Steine et al (2021) of 49,051 Norwegian students revealed a substantial positive correlation between sexual harassment, nightmares, and insomnia. According to the Diagnostic and Statistical Manual (DSM-4) and a survey conducted by Browne and Finkelhor (1986), university students have depression rates 12.9% higher than those of the general population.…”
Section: Sexual Harassment Of Female University Students and Their Pa...mentioning
confidence: 99%